Digital Vulnerability and the Formulation of Harmonised Rules for Algorithmic Contracts: A Two-Sided Interplay - Rodriguez, Teresa de Las Heras Ballell (The New Shapes of Digital Vulnerability in European Private Law, 2024)
This book provides an analysis on whether and how the current European legal framework adequately deals with personal conditions in which digital...

The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal - Kane, Ibrahima (The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On, 2024)
"Chapter 16 The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal" published on 09 Feb 2024 by Brill | Nijhoff.
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives; Social Sciences

Part XV Chapter 2, Conciliation beyond the courts: aspirations and limits of mandated and voluntary court mediation programmes from a multi-jurisdictional perspective - Ali, Shahla (Comparative Procedural Law and Justice, 2024)
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Climate Change Litigation in Civil Law African Countries: An Assessment of Barriers and Potentialities in Cameroon - Mbarga, Daniel Armel Owona (Climate Litigation and Justice in Africa, 2024)
It seems like a long time ago that there were only a handful of climate lawsuits. Since the first climate lawsuits were filed in the United States in 1990,² a myriad of litigation has emerged at the national, regional and global levels. According to the Grantham Research Institute on Climate Change and the Environment, as of May 2021 the databases on climate litigation around the world contained 1,841 cases that were either in progress or had already been decided.³ This shows the exponential development of the phenomenon through which civil society organizations, public law legal entities and private individuals are
Keywords: Africa; Cameroun; Civil Law; Climate change; Litigation

Questions spéciales du droit pénal fiscal d’entreprise - Muanda Nkole wa Yahve, Don José; Dashkevich, Zh V. (Esquisse du Droit pénal fiscal congolais, 2024)
T

Corporate Data Responsibility - Sarfaty, Galit A. (Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold, 2023)
This is an accepted manuscript of a book chapter in the edited volume: Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold

Chapter 1, Introduction to contract law and theory - DiMatteo, Larry A. (Principles of Contract Law and Theory, 2023)
This chapter provides background information on the evolution of the common law of contracts. It begins with a short history of the evolution of the common law in England including the roles played by the Roman Catholic Church, the development of a dual court system—one in law and the other in equity, the transition from absolute monarchy to a parliamentary form of government, the creation and restrictiveness of the English writ system, the common law’s reception in America, and the building of a general law of contract in the nineteenth century. It explains the historical differences between law and equity, along with the fusion of the two into a single court system. It also discusses the justifications given for contract law and its role in society. It describes the different perspectives of written or formal law, theory, and practice, and importantly, the difference between law in the books versus law in action. Finally, it explains the differences between rules, principles, and standards, and the boundaries of contract relative to other areas including tort and unjust enrichment.

Chapter 11, First principles in transportation law and policy - Levine, Jonathan; Shill, Gregory H. (A Research Agenda for US Land Use and Planning Law, 2023)
The main purpose of transportation is connecting people to destinations they value. This seemingly banal statement would, if taken seriously in policymaking, upend transportation and land use planning. Today, planning agencies rely on key performance indicators (KPIs) to measure outcomes. While ostensibly neutral and technical, these measurements in fact imply policy judgments and drive legal consequences. They operate both as a shield against litigation and as a sword to justify new projects. But the way KPIs are set up reflects confusion about basic purposes. They are used to plan and evaluate based not on the ability to reach anything but rather simply to accelerate the speed of traveling. We seek to anchor transportation policy discussion in first principles. The shift we propose is mode agnostic in that it is relevant to all means of transportation. Even so, shifting from a goal of speed to one of reachability would be a leap. We believe such a shift suggests important open questions regarding the barriers to reform and we engage a few of them.

Introduction: International Adjudication and the Legacy of the Mixed Arbitral Tribunals - Ruiz Fabri, Hélène (The Mixed Arbitral Tribunals, 1919–1939: An Experiment in the International Adjudication of Private Rights, 2023)
This introduction provides the reader with a general characterization of the 39 Mixed Arbitral Tribunals (MATs) created by the 1919-1923 peace treaties to address disputes between private persons and between private persons and states as a result of the First World War. Noting that the rich literature published on the MATs was followed by near-silence after 1945, it mentions the numerous questions that they still raise today, before explaining how the various contributions to the book edited by the authors address them.

Requisitos para la prestación de servicios de financiación participativa tras la situación generada por la Covid-19 - López Ortega, Raquel (El derecho mercantil y la pandemia: algunos problemas del pasado, la crisis coyuntural y las perspectivas futuras: libro homenaje a Agustín Madrid Parra, 2023)
El texto completo del libro en que se incluye este capítulo puede descargarse de: https://www.colexopenaccess.com/libros/derecho-mercantil-pandemia-problemas-pasado-crisis-coyuntural-perspectivas-futuras-5016

La mesure des sanctions en nature - Maire, Guillaume (Mesure(s) et droit, 2023)

La mise en concurrence des systèmes juridiques nationaux et l’idée de Constitution économique - Salah, M. Mahmoud Mohamed (The Idea of Economic Constitution in Europe, 2022)
Conséquence de la compétition que les États se livrent pour attirer le maximum d’investisseurs, la mise en concurrence des systèmes juridiques nationaux s’est traduite par une libéralisation continue du droit qui a eu un effet direct sur l’idée de Constitution économique. Celle-ci a non seulement vu son épaisseur normative se renforcer du fait de la neutralisation des dispositifs juridiques dirigistes mais elle s’est également universalisée en raison de la conversion de la quasi-totalité des pays au dogme de « l’attractivité ». Toutefois, ce mouvement généralisé vers le tout libéral commence à être remis en cause sous l’effet de facteurs divers qui se traduisent par une demande sociale et politique pour plus de régulation étatique. Il en résulte à la fois un regain de l’unilatéralisme qui affecte la force des principes qui sous-tendent l’idée de constitution économique et une prise en compte plus affirmée des valeurs et intérêts collectifs qui altère la substance de ces principes.
Keywords: Constitutional Law; Economic History; History; International Law; Legal History

Do corporate governance codes matter in Africa? - Areneke, Geofry; Khlif, Wafa; Kimani, Danson; Soobaroyen, Teerooven (Research Handbook on Corporate Board Decision-Making, 2022)
Africa is often depicted in the literature as the ‘patron late to the party’ on account of her low uptake of corporate governance codes. Notwithstanding, countries that have an existing corporate governance code continue to exhibit weak corporate accountability and governance practices. This prompted a critical analysis based on a detailed review of published articles and existing codes in the African multiple-contexts. Our findings reveal that the efficacy of many codes remains very limited in terms of pragmatic outcomes whilst firms in countries that have adopted codes continue to face uneven performance and poor accountability. We conclude by urging for an understanding of the reasons underlying such results. We recommend an African led re-think (independence, ownership, board processes) of existing codes to make them more aligned with the governance needs of African firms and their complex sociocultural background. We call for further research to illuminate Africa’s actual governance experiences and necessities.
Keywords: Africa; African principles; Board of directors; Boardroom processes; Codes; Corporate governance; Developing countries; Neo-colonialism

The (Domestic) Enforcement of AU International Economic Law Instruments: Exploring the Desirability of Direct Effect - Simo, Regis Yann (The Emergent African Union Law: Conceptualization, Delimitation, and Application, 2021)
This chapter deals with the principle of direct effect as applied in European Union law and explores its suitability in the enforcement of African Union (AU) legal instruments, notably those setting up the African Continental Free Trade Area (AfCFTA). What motivates the issue of direct effect is the noted reticence of African countries to litigate trade matters between themselves despite the existence of provisions of regional trade treaties creating courts of justice which give standing to Member States. Therefore, it surveys the avenues through which natural and legal persons can uphold their rights stemming from AfCFTA treaties thus contributing to treaty interpretation and increasing security and predictability. Currently, the AfCFTA Dispute Settlement Protocol, modelled after the WTO, does not allow such a possibility, contrary to rights acquired by natural and legal persons before some African Regional Economic Communities (RECs) courts. Nevertheless, this chapter finds that carving out access of natural and legal persons to AfCFTA proceedings may not always work as intended since there are other ways to bypass these obstacles. These loopholes could be the gateway through which direct effect will develop and become a principle of AU law broadly speaking. These gaps further complement this chapter’s suggestions to explore amending the AfCFTA legal instruments, even though its dispute settlement system is yet to be tested, in order to match the standing that natural and legal persons have acquired under the RECs, which, in fine, are building blocs towards achieving the AfCFTA and, eventually, the African Economic Community.
Keywords: AfCFTA; Africa; Direct effect; International Economic Law; International Law; International Trade Law; Regional courts; Regional integration

Chapter II: The Arbitrator and the Arbitration Procedure, An Arbitrator’s Imperative – How to Avoid Disappointing the Parties, Preventing Surprises and Enabling Efficient and Progressive Arbitral Proceedings - Welser, Irene; Mimnagh, Samuel (Austrian Yearbook on International Arbitration, 2021)

International Investment Law in African Courts - Mbengue, Makane Moïse; Schacherer, Stefanie (International Investment Law: An Analysis of Major Decisions, 2020)
This chapter identifies major categories of situations, events and institutions in which or through which questions of international investment law have been dealt with before African courts. The chapter is selective in nature and aims at showing tendencies instead of exhaustivity. A noteworthy tendency that becomes apparent through the chapter’s analysis is that the prevailing narrative of bypassing African courts and tribunals seems declining in importance as an increasing number of national investment law instruments foresee African judicial and arbitral institutions for the settlement of investment disputes.
Keywords: African national courts; Apartheid; EAC; ECOWAS; Investment arbitration; Land reform; National investment law; OHADA

Critical reflections on the development of integrated reporting: Are integrated reporting and IFRS competing frameworks? - Barker, R.; Teixeira, A. (The Routledge Handbook of Integrated Reporting, 2020)
Although integrated reporting emphasizes the contemporaneous relationship between financial and non-financial capitals, its primary purpose is to explain how an organization creates value over time. This is similar to the purpose of management commentary, which is part of a general-purpose financial report. We compare and contrast the information requirements of an integrated report with the type of information that supplements the primary financial information in general purpose financial reports, prepared in accordance with International Financial Reporting Standards (IFRS). We examine whether the information in those reports is intended to be forward-looking and predictive, whether non-financial capitals can (and should) be monetized in order to facilitate integration, and whether the reporting boundary should be drawn in different ways to serve different purposes. We find that the International Integrated Reporting Framework and IFRS do not serve different purposes or apply different approaches, but that – in essence – they are competing frameworks. While IFRS has highly developed standards for reporting financial capital, neither has a well-developed approach for reporting any other capital.

Les suites de l’accord amiable en afrique - Blanc, Gérard (L'accord amiable, 2020)